Enunciating Genocide: Crime, Rights and the Impact of Judicial Intervention - FINDLAY, Mark (Institutional Knowledge at Singapore Management University, 2013)
As a consequence of recent decisions from the ICJ and the ICTR, it is clear that genocide can be pursued through the international courts both in terms of criminal liability and also rights/responsibility legal paradigms. This article suggests that this duality in possible contexts and processes of judicial determination, while being procedurally problematic, is in keeping with the human rights direction of international criminal justice. In addition, by opening the legal consideration of genocide to questions of individual liability as well as state-sponsored rights abuse, judges are now able to consider the more realistic complexity of genocide atrocity and thereby to address the diverse legitimate interests of victims. Particularly, by enabling and expanding juridical activation as the medium for legally enunciating the Genocide Convention, the determination of genocide and its consequences may benefit from enhanced certainty when reflected against the constitutional legality of the courts.